The Relevance of Collaborative Governance in Disaster Anticipation in The Cities of Surabaya and Jakarta - Ernawati, Deasy; Istania, Ratri; Asropi, Asropi (Journal Public Policy, 2024)
This research aims to examine the relevance of collaborative governance in flood disaster management within the smart city frameworks of Surabaya and Jakarta. Both cities are identified as having the highest flood disaster risk, yet disaster risk reduction has not been integrated effectively into their smart city initiatives, and flood management remains sectoral. Using the CORE (Collaborative Resilience) analysis and a qualitative research approach, this study investigates the extent of collaboration in disaster management in these cities. The findings reveal that in Surabaya, where the population is more homogeneous, smart city initiatives function effectively even without significant collaboration between actors. However, in Jakarta, with its more heterogeneous population, the absence of collaboration presents greater challenges. The research also highlights that collaboration is a critical factor in the success of smart city implementation, as seen in both cities. Surabaya's bureaucratic approach to disaster management, though efficient in execution, can be slow in response. Meanwhile, Jakarta’s smart city infrastructure, though more advanced, suffers from a lack of long-term collaborative policies. The study concludes that population homogeneity in cities like Surabaya allows for easier collaboration, while the complexity in Jakarta demands a more integrated and collaborative governance framework for effective flood management. Further research is needed to explore these dynamics in other Indonesian cities.